Geopolitical Volatility Driven by Financial crisis: An Analysis of the 2008 Global Financial Crisis and its Geopolitical Consequences - Qureshi, Ahmed Mehmood (Future Science, 2025)
This study analyzes the 2008 Global Financial Crisis as a fundamental geopolitical event that reshaped global power structures and triggered extensive economic and political upheaval. Moving beyond conventional economic explanations, it applies multidimensional frameworks—including the Politics-Economics Collision, Doughnut Economy, Multi-Stakeholder Helix Models, and Agnew’s Three Ages of Geopolitics—to trace how the crisis evolved from a banking collapse into a systemic rupture of sustainability and governance. The crisis precipitated cascading effects such as the Arab Spring, the rise of populism and nationalism in the West, and the realignment of global power towards emerging markets like the BRICS. The study highlights critical governance failures, social-ecological breaches, and geopolitical volatility, offering lessons for integrating financial regulation with sustainable, equity-driven geopolitical strategy to enhance global stability and prevent future crises.